Spreading effect of tDCS in individuals with attention-deficit/hyperactivity disorder as shown by functional cortical networks: a randomized, double-blind, sham-controlled trial - Cosmo, Camila; Ferreira, Cândida; Miranda, José Garcia V.; do Rosário, Raphael S.; Baptista, Abrahão; Montoya, Pedro; de Sena, Eduardo P. (Frontiers in Psychiatry, 2015)
Transcranial direct current stimulation (tDCS) is known to modulate spontaneous neural network excitability. The cognitive improvement observed in previous trials raises the potential of this technique as a possible therapeutic tool for use in attention-deficit/hyperactivity disorder (ADHD) population. However, to explore the potential of this technique as a treatment approach the functional parameters of brain connectivity and the extent of its effects need to be more fully investigated. The aim of this study was to investigate a functional cortical network model based on electroencephalographic activity for studying the dynamic patterns of brain connectivity modulated by tDCS and the distribution of its effects in individuals with attention-deficit/hyperactivity disorder (ADHD). Sixty ADHD patients participated in a parallel, randomized, double-blind, sham-controlled trial. Individuals underwent a single session of sham or anodal tDCS at 1 mA of current intensity over the left dorsolateral prefrontal cortex for 20 minutes. The acute effects of stimulation on brain connectivity were assessed using the functional cortical network model based on electroencephalography (EEG) activity. Comparing the weighted node degree within groups prior to and following the intervention, a statistically significant difference was found in the electrodes located on the target and correlated areas in the active group (p<0.05), while no statistically significant results were found in the sham group (p ≥0.05; paired-sample Wilcoxon signed rank test). Anodal tDCS increased functional brain connectivity in individuals with ADHD compared to data recorded in the baseline resting state. In addition, although some studies have suggested that the effects of tDCS are selective, the present findings show that its modulatory activity spreads. Further studies need to be performed to investigate the dynamic patterns and physiological mechanisms underlying the modulatory effects of tDCS.